Magnetostratigraphic Analysis of Ferromanganese (Fe-Mn) Deposits - Hassan, Muhammad Bin (2023)
Ferromanganese (FeMn) deposits are iron oxyhydroxides and manganese oxides which precipitate on the seafloor over millions of years at a very slow growth rate. Their chemical, mineralogical, and textural variations reflect the paleoenvironmental conditions under which they form. This research was developed to conduct magnetic studies on Fe-Mn deposits recovered from the Rio Grande Rise (RGR) in the southwestern Atlantic Ocean, Tropic Seamount (TS) in the northeastern Atlantic Ocean and the Pacific Ocean. Magnetic, microscopic, and geochemical study of ferromanganese nodule sample JC120-104B collected from Clarion-Clipperton zone (CCZ) indicates the presence of biogenic magnetite (magnetofossils). The nodule sample shows distinctive alternating Mn and Fe-rich layers, the increase in magnetic properties is consistent with the increase in Mn content, which is related to favourable conditions for Mn precipitation as well as magnetite biomineralization in the oxic-suboxic transition zone. FeMn crusts develop on and around seamounts and are a source of essential metals and rare earth elements. The amorphous (non-crystalline) occurrence of Fe oxyhydroxides and the absence of Fe oxides in the recent fresh (hydrogenetic/non-phosphatized/unaltered) layers of FeMn crusts prevent developing a primary remanent magnetization. While magnetic study combined with the geochemical investigation is essential to understand paleoenvironmental changes, a robust magnetostratigraphic model for the studied FeMn crusts is difficult to obtain due to the absence and loss of primary magnetization. Since FeMn nodules and crusts from the Pacific Ocean contain biogenic magnetite produced by magnetotactic bacteria (MTB) as a primary remanence carrier, a magnetic study was conducted on quantified bacterial cells produced by distinct bacterial species. Magnetic properties of quantified bacterial magnetite depend on the quantity of MTB cells rather than on the bacterial species or cell type (lysed or whole). This study also estimates the carbon content of MTB cells and discusses its relationship to the global carbon cycle. In order to understand the relationship between the deposition of Fe and Mn, biogenic magnetite produced by MTB and environmental conditions, a study was conducted on an IODP core from the Great Barrier Reef (GBR), Australia. The magnetic mineralogical and geochemical data from IODP Expedition 325 - Hole M0058A reveals the depositional history of the GBR margin during the interval of MIS 7 to 5 and MIS 1. In this case, the deposition of Fe and Mn in mixed siliciclastic-carbonate sediments is related to terrigenous input, while the presence of biogenic magnetite is related to the arid climatic conditions. The arid periods over NE Australia were established after the glacial/interglacial transition and at the middle Holocene, favoring dust deposition and promoting primary productivity. The occurrence of Fe and Mn in distinct marine environments corresponds to different magnetic implications. The presence of biogenic magnetite in FeMn nodules and crusts is linked to the oxygenation conditions while the biogenic magnetite in mixed siliciclastic carbonate sediments is associated with the increase of primary productivity enhanced by arid climatic conditions.